PERANCANGAN APLIKASI PENGOLAHAN CITRA DIGITAL UNTUK MENENTUKAN BIBIT UNGGUL BIJI KOPI DENGAN METODE CANNY EDGE DETECTION - Batubara, Sandrak A (STMIK Budi Darma, 2020)
The image of coffee beans is very important to recognize, with the image of coffee beans will make coffee lovers easier to recognize the coffee beans just by looking at their image without having to locate where the coffee grows. Coffee is a beverage known in Indonesia, the detection of coffee beans is very important because the number of seeds that are similar to coffee beans, so the process of detecting coffee beans is very necessary so that coffee beans can be identified, with the method of cany can detect real coffee beans. The cany method is a method that can detect coffee beans by recognizing the coffee beans.